Seventy-two Cycles of FOLFIRINOX: Long Term Treatment in a Patient with Metastatic Adenocarcinoma of the Pancreatic Tail - Tiller, Maximilian; Gundling, Felix; Schepp, Wolfgang; Fuchs, Martin (JOP. Journal of the Pancreas, 2015)
Context Pancreatic adenocarcinoma is one of the most lethal malignancies worldwide. In patients with unresectable tumor there are several strategies of palliative chemotherapy, either gemcitabine based regimens or FOLFIRINOX, which is supposed to be most efficient but also most toxic. Hence, management of toxicity is crucial to perform a therapy consisting of FOLFIRINOX. Case report We report on a 69-year-old female patient suffering from adenocarcinoma of the pancreatic tail with multiple liver metastases. Palliative chemotherapy comprising leucovorin, fluorouracil, oxaliplatin and irinotecan (FOLFIRINOX) was initiated in February 2011 and was tolerated very well. Subsequent computed tomography–scans showed significant reduction of the tumor load in the liver as well as in the primary pancreatic tumor. The serum levels of the tumor marker CA 19-9 were elevated initially and decreased concomitantly. Thus, chemotherapy was continued for more than 3 years, and up to 72 cycles were administered until April 2014. Due to intermittent neutropenia and mucositis the initial dose was reduced to 60% of the calculated standard dose. In April 2014, an intermediate staging by computed tomography and FDG-PET revealed significant reduction of the size of the primary pancreatic tumor compared with February 2011. Liver metastases could hardly be detected anymore. After pausing chemotherapy for 12 weeks, one liver metastasis reappeared and was treated by RFA in August 2014. Meanwhile, in October 2014 there is no radiological evidence on any existing tumor or metastasis. Conclusion Our report demonstrates that a sufficient tolerance of chemotherapy with FOLFIRINOX is achievable, what makes a long term treatment with FOLFIRINOX feasible and can lead to impressive results. Image: Laboratory parameters during chemotherapy.